Bio-Polymers, Ceramics, Glasses Corrosion and Properties of Biomaterials - - 4, Theme (Recent Research in Science and Technology, 2010)
Proceedings of "Conference on Recent Advances in Biomaterials Dec 17-18 ’10" Held at Saveetha School of Engineering, Saveetha University, Thandalam, Chennai-602 105, Tamilnadu, India Theme 4 Â Bio-Polymers, Ceramics, Glasses Corrosion and Properties of Biomaterials